MINAT SISWA SDN 3 RUMBUK KECAMATAN SAKRA KABUPATEN LOMBOK TIMUR TERHADAP CABANG OLAHRAGA TENIS MEJA - Muhammad Rosyihan Anwar; Johan Irmansyah; Aminullah (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2023)
Interest is the driving force that encourages individuals to engage in activities they enjoy and is stable, related to the rights they are interested in. This study aims to determine the interest of students at SDN 3 RUMBUK, Sakra District, East Lombok Regency, in table tennis sports. This descriptive research was conducted in April 2024 with a sample of 42 students selected through random sampling. Data were collected using questionnaires and analyzed quantitatively using percentage formulas. The results show that for the attention indicator, 48% of students were categorized as very good, 51% as good, and 1% as moderate; for the liking and interest indicator, 48% were very good, 51% good, and 1% moderate; for the activity indicator, 48% were very good, 51% good, and 1% moderate; for the teacher and coach role indicator, 49% were very good, and 51% were good; for the facility indicator, 48% were very good, and 52% were good; for the family indicator, 35% were very good, and 65% were good; for the environment indicator, 41% were very good, and 59% were good. The conclusion of this study is that the interest of students in table tennis sports at SDN 3 RUMBUK falls into the good category with the highest percentage. Keywords: student interest, table tennis, sports, elementary school, quantitative analysis. Minat adalah kekuatan pendorong yang mendorong seseorang untuk terlibat dalam aktivitas yang disukainya dan bersifat stabil terkait dengan hak yang diminatinya. Penelitian ini bertujuan untuk mengetahui minat siswa SDN 3 RUMBUK, Kecamatan Sakra, Kabupaten Lombok Timur terhadap olahraga tenis meja. Penelitian deskriptif ini dilakukan pada April 2024 dengan sampel 42 siswa yang diambil secara random sampling. Data dikumpulkan melalui angket dan dianalisis secara kuantitatif menggunakan rumus persentase. Hasil penelitian menunjukkan bahwa pada indikator perhatian, 48% siswa berada pada kategori sangat baik, 51% baik, dan 1% sedang; pada indikator rasa suka dan tertarik, 48% sangat baik, 51% baik, dan 1% sedang; pada indikator aktivitas, 48% sangat baik, 51% baik, dan 1% sedang; pada indikator peran guru dan pelatih, 49% sangat baik, dan 51% baik; pada indikator fasilitas, 48% sangat baik, dan 52% baik; pada indikator keluarga, 35% sangat baik, dan 65% baik; pada indikator lingkungan, 41% sangat baik, dan 59% baik. Kesimpulannya, minat siswa terhadap olahraga tenis meja di SDN 3 RUMBUK berada pada kategori baik dengan persentase tertinggi